Current Perspectives on Less-known Aspects of Headache - Turker, Hande (IntechOpen, 2017)
Headache, as a main neurological problem in everyday life, still takes place as a contributor on top of the list of many partially solved neurological conditions. Not only primary headaches but secondary headaches are still clinical concerns of diagnosis, differential diagnosis, and therapy. This book is quite different from classical headache books. First of all, it does not contain the classical schema of a classical headache textbook. Most of the chapters composing this book contain many answers for many unanswered questions about headache in general, for example, "Is headache a genetic condition?", "What do smartphones do to our brains? Do they cause headaches?", and "Does botulinum toxin really improve chronic migraine?". We hope this book will be an interesting read and perhaps a guide in some new aspects of headache and help understand "some interesting headache issues" while stressing some of the less known mentioned above.